Prey conditions, food habits, and their relationship to the catch of Penaeus merguensis De Man, 1888 in the waters of Merauke District, Indonesia - BONNY LANTANG; NAJAMUDDIN NAJAMUDDIN; ALFA FILEP PETRUS NELWAN; MUHAMMAD FARID SAMAWI (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Lantang B, Najamuddin, Nelwan AFP, Samawi MF. 2024. Prey conditions, food habits, and their relationship to the catch of Penaeus merguensis De Man, 1888 in the waters of Merauke District, Indonesia. Biodiversitas 25: 1554-1569. The study of the food habits of commercial crustaceans, namely Penaeus merguensis De Man 1888 in the waters of Merauke District was limited. Hence, research related to this was needed. For this reason, the study aims to analyze the prey fragment, prawn food habits, and their relationship to the catch based on differences in habitat types in the coastal waters of Merauke District. Data measuring oceanographic parameters, gastric contents samples of banana prawn (P. merguensis), mollusk samples, and catches were taken twice monthly in five habitats from March 2022 to March 2023. The results showed that for the fragmentation of prey, namely microalgae, 76.12% was found intact, while mollusks were found 97.46% not intact or dismembered. Mangrove leaves, macrophytes, prawn larvae, and fish larvae were found to be 100% incomplete or dismembered. Microalgae and mollusks were the main food in estuarial habitats and sandy beaches in Lampu Satu. While in mangrove habitats in Yobar, sandy beaches in Payum, and mangrove habitats in Bokem, the main food is mollusks, and complementary foods are microalgae. Mangrove leaves, macrophytes, prawns, and fish larvae were found only as supplementary food in all habitats. This was related to the availability of food that varies in each habitat. The catch increased with the discovery of the food habits of mollusks.